"Contradiction" as a Peculiarity of Dostoevsky's Artistic Thinking - Serdiuchenko, V. (Literatūra, 1975)
The article deals with one of the most discussed aspects of the study of Dostoevsky - the problem of the peculiarities of his artistic thinking. The author dwells on the fanciful presence in his writings of open tendency side by side with the ideas hostile to the writer's outlook, and comes to thP. conclusion that this ideological "polyphonism" of Dostoevsky is not his artistic selfaim (M. Bakhtin) but the writer's poetical means to reveal ideological collisions of his age.
Keywords: -